Dosimetric evaluation of X-ray examinations of paranasal sinuses in pediatric patients - Cantalupo,Beatriz de Lucena Villa-Chan (2016)
Abstract Objective: To estimate the entrance surface air kerma (Ka,e) and air kerma in the region of radiosensitive organs in radiographs of pediatric paranasal sinuses. Materials and Methods: Patient data and irradiation parameters were collected in examinations of the paranasal sinuses in children from 0 to 15 years of age at two children's hospitals in the city of Recife, PE, Brazil. We estimated the Ka,e using the X-ray tube outputs and selected parameters. To estimate the air kerma values in the regions of the eyes and thyroid, we used thermoluminescent dosimeters. Results: The Ka,e values ranged from 0.065 to 1.446 mGy in cavum radiographs, from 0.104 to 7.298 mGy in Caldwell views, and from 0.113 to 7.824 mGy in Waters views. Air kerma values in the region of the eyes ranged from 0.001 to 0.968 mGy in cavum radiographs and from 0.011 to 0.422 mGy in Caldwell and Waters views . In the thyroid region, air kerma values ranged from 0.005 to 0.932 mGy in cavum radiographs and from 0.002 to 0.972 mGy in Caldwell and Waters views. Conclusion: The radiation levels used at the institutions under study were higher than those recommended in international protocols. We recommend that interventions be initiated in order to reduce patient exposure to radiation and therefore the risks associated with radiological examination of the paranasal sinuses.